Trade statistics of the Irish Free State in 1924: introduction [to Symposium] - Oldham, C. H. (Statistical and Social Inquiry Society of Ireland, 1925)
The Irish Free State is a new world economic unit. Our business at this meeting is to consider the Trade Statistics of the Irish Free State for 1924, which is the first evidence we have got as to its actual stature both as a producer and a consumer. This Grey Book, published in March, 1925 (price 2s.), must here be taken as read. By various contributions we now propose to discuss what this new evidence amounts to, what it proves as to the economic connections of the Irish Free State with other countries.
Symposium on the trade statistics of the Irish Free State in 1924
Read Friday, 1st May, 1925
Keywords: Irish Free State; Trade statistics; 314.15